Analisis Nilai Pendidikan Karakter Dalam Film Sang Prawira Yang Disutradarai Oleh Ponti Gea - Titis Laksana Nurrohmad; Adyana Sunanda (JURNAL MANAJEMEN PENDIDIKAN, 2026)
ANALYSIS OF CHARACTER EDUCATION VALUES IN THE FILM SANG PRAWIRA DIRECTED BY PONTI GEA The purpose of this study is to describe the Value of Character Education in the Sang Prawira Film directed by Ponti Gea. This study uses a descriptive approach to qualitative research. The object of this study is the Sang Prawira Film directed by Ponti Gea. The data collection technique used is by observing and taking notes. The data analysis technique is carried out by looking for dialogue scenes that describe the value of character education. The values ​​of character education that researchers found include religious values, tolerance values, honest values, hard work values, democratic values, social care values, national spirit values, discipline values, values ​​of appreciating achievement, communicative values, creative values, values ​​of love for the homeland and values ​​of responsibility.